The relationship between family support and the quality of life of patients with seroconcordant HIV at the Pandian health center and Pamolokan health center, Sumenep Regency - Fikri, M.Kep, Zahid; Dwi Kurnia, Anggraini; Sunardi, Sunardi; Arfianto, Muhammad Ari; ‘Ibad, Muhammad Rosyidul; Kholis, Moh. Agung Nur; Mu'jizah, Khikmatul; Toonsiri, Chanandchidadussadee; Wijaya Ridi Putra, Kusuma (Jurnal Keperawatan, 2023)
Introductions: The HIV/AIDS endemic infected millions worldwide in 2019. Indonesia reported a very significant case of the disease, where East Java occupies the fourth position out of all the provinces. People who suffer from this disease (ODHA) are often associated with a poor quality of life. Family support is needed to control the patient's disease and improve the patient's quality of life. Objectives: This study aims to determine the relationship between family support and the quality of life of seroconcordant HIV patients. Methods: The study design used cross-sectional with a sample of 36 seroconcordant PLHIV patients and 32 people who met the inclusion criteria (living with family, married, and registered at the Sumenep District Health Center). The data collection instrument used the "family support" questionnaire and WHOQL-HIV Bref. The collected data were analyzed using the Rank Spearman technique at a significance level of 0.05. Results: The results of this study showed that more than half of the respondents (59.4%) received "good" family support; the majority of respondents (78.1%) have a “fairly good” quality of life; and there is a significant relationship between the two variables as evidenced by the p-value = 0.002 which has a "strong" relationship strength as evidenced by the correlation coefficient = 0.520 and has a unidirectional relationship as evidenced by the positive correlation coefficient. The more family support is improved, the quality of life of the respondents will increase. Conclusion: There is a significant, strong, and one-way relationship between family support and the quality of life of seroconcordant HIV patients. Families should increase their support for HIV patients to improve their quality of life in everyday life.